Agro-ento bioinformation: towards the edge of reality - Syed Hassan, Syed Tajuddin (2002)
Information communication has advanced from the fundamental universe-bio-physicschemistry probes to exploration of bioprocessing tangibles and intangibles. Bounded by such information advancement frames, domains of agro-forestry and entomology, and medicine, have witnessed progression through evolution, revolution, and bioinformation in their knowledge contents. Integrated Pest Management (IPM) paradigms steered the course of agro-forest and medical-industries during the 1800 and 1900 eras. IPM Concept is a synthetic framework that results from evolution, revolution, and presently bioformation in domains of agro-medico-ecological and anthropo-ecological activities. A chronological history of pest management parallels the history of industrial revolution and highlights man's attempts at dealing and living with the environment, arthropods and other pestly species. A cycle of progression from using natural controls to made-made utilities and back to enhancing of natural processes is evident as one walks through time and space of history during the development of civilization. IPM success demands usage and stringent compliance with ecological imperatives, which need to be lucidly expressed as knowledge precepts. Biological knowledge is at the forefront of this usage, especially with the new millennium becoming the Age of Biology. Consequently, bioinformation is commencing to thrive as a global entity, which revolutionizes and drives societal progress. Bioinformation, in brief, comprises biology, information algorithms, information technology, and communication protocols. Thus biology becomes a domain of information science. Attributes of bioinformation can be defined through its primers and profiles. The primers, which entrain processes, both natural and man-induced, include mechanisms such as protocols, algorithms, visualisations, and structural and visual designs. The protocols range from the molecular levels to domains of larger dimensions such as those encompassing fraternities of politics and policies, and societal applications. These protocols, algorithms, and visualisations undergo dynamic incubation processes to produce the end product, which is bioinformation. Entomology is an inherent component of this bioinformation revolution. The information communication technology linkages are exemplified through simulation, modelling, and visualization explorations.